Ten years later: Lessons for DSGE builders and Czech policy makers - Aleš Michl (Review of Economic Perspectives, 2019)
We show an example of a small open economy - the Czech Republic - where the fiscal restriction was put in place between 2010 and 2013 in a negative output gap and zero lower bound on nominal interest rates. According to our results, such fiscal policy seems to have been mistaken, as the restriction may apparently have caused a second recession in the Czech Republic in 2012/2013 (after the global recession in 2008/2009). Instead of the dynamic stochastic general equilibrium approach (DSGE), we applied a tractable static deterministic partial equilibrium approach using the IS-LM framework. We derived mathematically from the IS-LM model that expansionary fiscal policy acting via higher government investment can be an appropriate tool for reacting to a crisis in the very short run when interest rates hit the zero lower bound. Expansionary fiscal policy after the 2008/2009 crisis would probably have led to faster stabilisation of the Czech economy. We simulate a potential increase in government investment of 8% yearly between 2011 and 2013. This would have added 0.4 pp to GDP growth and increased the inflation rate by about 0.5 pp. Hence, the inflation outlook in 2013 would not have been negative and would consequently have led to less pressure for monetary policy expansion using unconventional interventions against the Czech koruna.
Keywords: E12; E41; E44; E62; 330; IS-LM model; DSGE; zero lower bound; fiscal policy; monetary policy